Numerical solution of boundary layer problem due to moving flat plate using Runge-Kutta methods - Syed Abdul Kadir, Syed Khalid (2007)
This project is carried out to investigate the flow characteristic of boundary layer over moving plate using numerical solution. The flow characteristic along moving flat plate can be identify using numerical solution of the boundary layer equation. The numerical technique that was used in this project are Runge-Kutta methods. The steady flow, two dimensionless flow, incompressible flow, infinite aluminum flat plate and laminar flow was consider in this project. The programming of the boundary layer equation are developed. The programming was developed using the FORTRAN90 software and compiled by FORTRAN Power Station 4.0. The velocity profile of boundary layer along moving flat plate are investigated. It can be seen that when the flow distance from plate are increases, the velocity in boundary layer will decrease and the wall shear stress will increase. The comparison also been made with Blasius flow and previous study result. The flow characteristic of moving flat plate had been solve numerically using numerical approach.